Frontispiece: π‐Concave Hosts for Curved Carbon Nanomaterials. Issue 27 (10th May 2019) - Selmani, Serxho; Schipper, Derek J.
Abstract : π‐Concave hosts have proven to be an invaluable tool in the purification and application of fullerenes and carbon nanotubes. The unique host–guest shape matching has created a field of research that is dedicated to understanding and maximizing these interactions. Through slight alterations in host design, profound differences in binding emerge. In their Minireview on page 6673 ff., S. Selmani and D. J. Schipper shed light on the dynamic effects of these various changes by providing an overview of the current literature. Furthermore, they offer a checklist of the various factors that can be used to influence the binding of π‐concave hosts with π‐convex carbon nanomaterials.